PERAN EMOSI POSITIF SEBAGAI PEMEDIASI PENGARUH STIMULUS TOKO TERHADAP IMPULSE BUYING PAKAIAN DI MATAHARI DEPARTMENT STORE KUTA SQUARE - Budiharta, Kadek; Santika, I Wayan (E-Jurnal Manajemen, 2015)
The purpose of this study was to determine the role of positive emotions as a stimulus influences pemediasi shop towards impulse buying clothes in Kuta Square Matahari Department Store. This study uses qualitative research is by using observation and questionnaires to 140 buyers in Kuta Square Matahari Department Store. The data analysis technique used is structural equation modeling (SEM). Obtained findings that stimulus variables store positive and significant effect on impulse buying. Furthermore, the stimulus variable store positive and significant effect on positive emotions. Variable positive emotions positive and significant effect on impulse buying. Finally, a significant effect of positive emotions in mediating stimulus to the store impulse buying.
Keywords: Stimulus Toko; Emosi Positif; Impulse Buying